Parental Patterns In Educating Early Childhood Emotional Development - Satrial, Ardi; Fitriana, Delita; Rahmi, Elvi; Arifin, Zainul (Journal of Islamic Early Childhood Education, 2025)
This study aims to describe parenting patterns in educating the emotional development of early childhood at PAUD Al-Amin Lubuk Alung and identify the role of the family and school environment in shaping children's social-emotional abilities. The research approach used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers, parents, and students at PAUD Al-Amin. The results show that the emotional development of early childhood is strongly influenced by the parenting patterns applied by parents. Children who receive democratic parenting patterns show better abilities in recognizing and managing emotions, empathizing, and interacting socially positively. Meanwhile, children who are raised with an authoritarian pattern tend to have difficulties in controlling emotions and behave aggressively. The family and school environment play an important role in providing positive examples and habits to support children's social-emotional development. This study concludes that the synergy between appropriate parenting patterns, open communication within the family, and a supportive school environment is a key factor in shaping the emotional character of early childhood that is healthy and balanced.